PHYSICOCHEMICAL CHARACTERIZATION AND HEPATOPROTECTIVE ACTIVITY OF MANDUR BHASMA - Gawate, Reshma P.; Kilor, Vaishali A.; Sapkal, Nidhi P. (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: Bhasmas are traditional Indian medicinal preparations that are standardized using quality control tests prescribed by Ayurveda and other guidelines. There is a need to study the adequacy of the existing quality control tests and to correlate these to the performance of the product. No attempt has been made in the literature to study the adequacy of these tests in determining the biological activity of a product and to suggests new analytical techniques for determining the quality. In the present work, an attempt has been made to compare marketed samples of Mandur bhasma with respect to various existing quality control tests and to analyze these samples using modern analytical techniques for the complete analysis of Mandur Bhasma. Adequacy of all the tests and techniques was studied with respect to the hepatoprotective activity of mandur bhasma in paracetamol induced hepatotoxicity in rats. Methods: The marketed products of three leading brands of Mandur Bhasma were analyzed for quality-control tests as prescribed by Ayurveda and other guidelines. These samples were also analysed using modern analytical techniques like AAS, IR, XRD, HPTLC, SEM. These formulations were then evaluated for their hepatoprotective activity in paracetamol induced hepatotoxicity in rats and the results obtained were correlated with analytical results. Results: It was found that all the three bhasma samples were passing in quality control tests as prescribed by Ayurveda and other guidelines. These samples produced similar results when analyzed using AAS and IR. The results were different when analyzed using colorimetry, HPTLC, SEM and XRD. The extent of hepatoprotection in rats with paracetamol induced hepatotoxicity was also found to be different in the three samples. Conclusion: The analysis was carried out on three different marketed samples, and a correlation has been reported. It was seen that although all the three formulations passed traditional quality control tests and the tests laid by regulatory guidelines, but still there were significant differences in their biological activity. Analysis of iron content using colorimetric method was found to be discriminating in estimating the biologically effective form of iron. It was also found that HPTLC, XRD and SEM should be further developed and validated as analytical tools in determining the quality of Mandur bhasma product. Keywords: Mandur bhasma, Colorimetry, IR, AAS, SEM, XRD, HPTLC, Hepatoprotective activity